2005
DOI: 10.1021/cg050160s
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Cinnamic and α-Truxillic Acids:  New Additions to an Old Story

Abstract: X-ray structure determinations have been carried out and analyzed for two conformational polymorphs of α-truxillic acid (2). Polymorph I (cell parameters known since 1959) is isolated upon recrystallization of 2 from acetic acid−petroleum ether solution, while polymorph II (fully characterized in 1993) is the product of a one-phase solid-state reaction of tail-irradiated α-cinnamic acid. For polymorph II, two redeterminations of mixed crystals containing solid solutions of α-cinnamic acid and 2 (68.1 and 89.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 39 publications
6
96
0
Order By: Relevance
“…However, in a recent determination of β-polymorph [45] the molecule adopts an s-cis conformation. This may raise the question about the polymorph present in the commercial sample.…”
Section: Conformational Preferences For the Isolated Molecule And Thementioning
confidence: 99%
“…However, in a recent determination of β-polymorph [45] the molecule adopts an s-cis conformation. This may raise the question about the polymorph present in the commercial sample.…”
Section: Conformational Preferences For the Isolated Molecule And Thementioning
confidence: 99%
“…It has antibacterial, antifungal and antiparasitic properties, and its derivatives are an important pharmaceuticals for high blood pressure and stroke prevention having antitumour activity [2][3][4][5]. From the survey of literature, it follows that there are articles that mainly deal with the study of cinnamic acid structure, its properties, derivatives and complexes with alkali metals, such as Zn(II), Hg(I), Hg(II), Cd(II), and Zn(II) [2][3][4][5][6][7][8][9][10]. Having very important biological activity and specific structure, cinnamic acid has been still extensively and solidly studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that excitation wavelengths close to the absorption maximum can lead to the pump light being too strongly absorbed in the outer layers of the crystal, effectively blocking it from reaching the centre of the sample and thus limiting the photo-conversion level. 47,48 To avoid this, a wavelength in the tail of the main absorption band is generally preferable. For 1ÁTHF, a series of LED wavelengths between 390 and 500 nm were initially tested (see ESI †).…”
Section: A Preliminary Experimentsmentioning
confidence: 99%